An Autonomy-Oriented Paradigm for Self-Organized Computing - Liu, Jiming; Gao, Chao; Zhong, Ning (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 02, 2009)
A bottom-up computing paradigm, namely Autonomy-Oriented Computing (AOC), offers some principles and mechanisms for non-linearly solving computationally hard problems. The goal of this paper is to describe how AOC-based emergent computing can be realized in large-scale, dynamic, distributed and/or decentralized networks. A case study is given to demonstrate the main process and contribution of self-organization, the core of AOC, in a distributed local search algorithm.